(untitled) (International Journal of Biomedical and Advance Research, 2020)
This paper deals with the documentation of the plants of Sikkim Himalayas that are having traded values. Our study reveals that these species are grown at various altitudes and are used for a variety of purposes. Species like Swertia chirayita, meant for its anti-diabetic, hepato-protective, antimalarial and anti-inflammatory properties is traded in large quantities at both national and international markets. Similarly, Sikkim is the largest producer of Amomum subulatum contributing up to 88% of India’s total cardamom production, where India is considered as the largest producer. Likewise, the leaves of Rhododendron campanulatum are exported from Sikkim as it is mixed with tobacco, used as snuff and cures cold and hemicrania. As a result of this, there is a high demand of these plants in the market and hence they are in danger of economic exploitation from wild habitants. Therefore, in order to conserve and safeguard the wild populations, commercial cultivation is required to meet up the market demand.